2001
DOI: 10.1080/07315724.2001.10719185
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Hazards of Antioxidants: Controlling Apoptosis and Other Protective Mechanisms in Cancer Patients and the Human Population

Abstract: Cellular oxidants, called reactive oxygen species (ROS), are constantly produced in animal and human cells. Excessive ROS can induce oxidative damage in cell constituents and promote a number of degenerative diseases and aging. Cellular antioxidants protect against the damaging effects of ROS. However, in moderate concentrations, ROS are necessary for a number of protective reactions. Thus, ROS are essential mediators of antimicrobial phagocytosis, detoxification reactions carried out by the cytochrome P-450 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
223
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(238 citation statements)
references
References 34 publications
6
223
0
9
Order By: Relevance
“…Selenium plays critical roles in major metabolic pathways, and is an essential element to protect the body from harmful substances. Recent studies demonstrated that selenium supplementation reduces side effects from chemotherapy and improves kidney and liver functions in cancer patients 16, 19, 20. Analysis of selenium intake by participants in our study revealed inverse associations with RCC risk for both EA and AA, with greater protective effects among AA.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Selenium plays critical roles in major metabolic pathways, and is an essential element to protect the body from harmful substances. Recent studies demonstrated that selenium supplementation reduces side effects from chemotherapy and improves kidney and liver functions in cancer patients 16, 19, 20. Analysis of selenium intake by participants in our study revealed inverse associations with RCC risk for both EA and AA, with greater protective effects among AA.…”
Section: Discussionsupporting
confidence: 50%
“…Many vitamins from diet and supplements, including vitamin A, C, and B, have been shown to have antioxidative effects and may influence RCC risk 5, 6, 7, 8, 14, 15. Intake of dietary E vitamins, including α‐, β‐, δ‐, and γ‐tocopherol, is suggested to be chemo‐preventative 16. Supplementation with selenium may influence RCC risk, and selenium has been shown to possess anti‐tumor functions 17, 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Despite controversy surrounding evidence of benefits of high-dose vitamin C supplementation for prolonged cancer survival (32)(33)(34) , our results showed prior to seasonal weighting that women with any type of cancer were more likely to be high-dose vitamin C supplement takers than women with no history of cancer. Since antioxidants can potentially reduce the effectiveness of anti-cancer drugs (35,36) , patients should be encouraged to discuss their supplement use with their doctors in order to avoid contraindications. For some cancer patients, supplement use may be a coping behaviour and a way of taking control (37,38) .…”
Section: Discussionmentioning
confidence: 99%
“…Espéci-es reativas de oxigênio, em moderada concentração, são mediadores essenciais de reações pelas quais o corpo livra-se de células indesejáveis. Sendo suplementos antioxidantes redutores de radicais livres, provavelmente ocorra interferência nos mecanismos essenciais de defesa para livrar o organismo das células defeituosas, incluindo aquelas que são pré-cancerosas e cancerosas (24) . Sendo assim, suplementos vitamínicos podem ser nocivos (19)(20)(21)(22)(23)25) .…”
Section: Complicações Relacionadas Ao Uso Indiscriminado De Antioxidaunclassified
“…Por outro lado, depois de décadas de uso para prevenir e combater doenças sistêmicas, vários relatos demonstram que o uso indiscriminado de antioxidantes pode ser extremamente maléfico à saúde (19)(20)(21)(22)(23)(24)(25)(26)(27) .…”
Section: Introductionunclassified